Information Security Awareness Analysis of the Threat of Data Leakage in Educational Institutions with the ISO 27001 Framework - Muhammad Rijal, Demas; Assydiqi, Mukhamad Fahmi; Prasetya, Yoel Rensisko; Prasetya Ningsih, Lidya Nurhapsari; Putri Anindra, Nisya Kayla; Pambudi, Pandu Dwi Luhur (Journal of Digital Business and Innovation Management, 2024)
In the rapidly evolving digital era, information security has become a major concern for various organizations, including educational institutions that are facing pressures such as "publish or perish" and performance metrics like VOS viewer. Serious threats such as cyber-attacks and data breaches require more advanced security solutions. Implementing an Information Security Management System (ISMS) based on ISO 27001 standards is crucial in safeguarding information assets. This research discusses the importance of information security awareness, identifies threats to data protection, and applies ISO 27001 standards in the context of educational institutions. The research methodology employs the PRISMA guideline to evaluate related reviews and meta-analyses systematically. Information security awareness, data protection, and ISO 27001 compliance focus on building a robust information security system within educational institutions facing performance and assessment demands.